2019
DOI: 10.1155/2019/6039147
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Apneic Events in Obstructive Sleep Apnea Associated with Acute Coronary Syndrome

Abstract: Background Obstructive sleep apnea (OSA) is a potential cardiovascular risk factor. However, there is currently no prominent screening strategy for its diagnosis in patients with acute coronary syndrome (ACS). The aim of this study was to establish the impact of apneic events in case of OSA associated with ACS. Methods Between January 1st and June 30th, fifty-three subjects with ACS (first acute myocardial infarction) were prospectively evaluated for OSA. Each patient was evaluated by polysomnography (PSG) two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…The pathophysiologic mechanism blamed for this relationship is based on endothelial dysfunction, coronary plaque burden, chronic inflammation and sympathetic activation secondary to intermittent hypoxemia [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pathophysiologic mechanism blamed for this relationship is based on endothelial dysfunction, coronary plaque burden, chronic inflammation and sympathetic activation secondary to intermittent hypoxemia [28].…”
Section: Discussionmentioning
confidence: 99%
“…Calcaianu et al . [28] performed polysomnography on patients with ACS 2 months after AMI and used the apneic coefficient (AC), defined as the ratio between apnea index and apnea-hypopnea index (AHI), as the main outcome. The results showed that the patients with a higher AC (≥37% vs. <37%) had higher baseline levels of troponin-I, N-terminal prohormone brain natriuretic peptide and higher SYNTAX scores, lower LVEF, and were more likely to have a STEMI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it is worth noting that the relationship between OSA and myocardial markers is complex, with contradictory findings in the literature. Some studies have reported lower troponin levels in OSA patients presenting with AMI, suggesting a cardioprotective effect [31]. Additionally, meta-analyses have failed to identify significant differences in troponin, CK, and CK-MB levels between cardiovascular disease patients with and without OSA [32].…”
Section: Discussionmentioning
confidence: 99%
“…Calcaianu et al found that a higher frequency of apneic events (AI/AHI) is associated with increased levels of troponin-I and NT-proBNP in patients with acute coronary syndrome (ACS). 34 The association between apneic events and future CVD risk may be due to apnea leading to more severe SpO 2 desaturation than hypopnea. Additionally, compared with hypopnea, increased inspiratory efforts against a completely closed airway during apnea create greater negative intrathoracic pressures and elevated venous return, which in turn overloads the right ventricle and increases the afterload on the left ventricle.…”
Section: Discussionmentioning
confidence: 99%